2009
DOI: 10.1111/j.1600-0625.2008.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilomatricoma can differentiate not only towards hair matrix and hair cortex, but also follicular infundibulum, outer root sheath and hair bulge

Abstract: Pilomatricoma is believed to differentiate towards the hair matrix and hair cortex. To elucidate the origin of differentiation in pilomatricoma, we studied the expression of epithelial keratin (K) and filaggrin (filament aggregating protein) in pilomatricoma. An immunohistochemical study has been made of 53 cases of pilomatricoma using 10 monospecific anti-keratin antibodies and anti-filaggrin antibody. Basophilic cells, transitional cells and shadow cells did not react with epithelial keratins and filaggrin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…There are various components showing TD or cell death inside the nodules by one of the following routes [42, 43]: (a) SCD, the main route of cell death/differentiation, (b) conventional apoptosis, and (c) EK/TK (Fig. 2).…”
Section: Shadow Cell Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various components showing TD or cell death inside the nodules by one of the following routes [42, 43]: (a) SCD, the main route of cell death/differentiation, (b) conventional apoptosis, and (c) EK/TK (Fig. 2).…”
Section: Shadow Cell Differentiationmentioning
confidence: 99%
“…2, inset). TK is rarely observed in PMX [43]. The nodule containing equal amounts of SCD and EK components is called an infundibular matrix cyst or hybrid cyst [44].…”
Section: Shadow Cell Differentiationmentioning
confidence: 99%
“…Keratin is found as intermediate‐sized filaments and is a differentiation marker of epithelial tumor 5 . Filaggrin, filament aggregating protein, is a major component of keratohyaline granules and is a marker of terminal differentiation 6 .…”
Section: Keratin and Filaggrin Profiles In The Normal Skin Epidermamentioning
confidence: 99%
“…The patient had no familial history of Gardner’s syndrome and did not have colonic polyposis. Excised specimens underwent immunohistochemical study with epithelial keratins and filaggrin using the labeled streptavidin biotin (LSAB) method as reported previously 5 . The anti‐keratin antibodies and anti‐filaggrin antibody used were 34βB4 (K1), LP5K (K7), LP3K (K8), HP1 (K10), LL002 (K14), LHK15 (K15), LL025 (K16), E3 (K17), 5D3 (K18), b170 (K19) and 15C10 (filaggrin) (all from Novocastra Laboratories, Newcastle‐upon‐Tyne, UK) 5 …”
Section: Keratin and Filaggrin Profiles In The Normal Skin Epidermamentioning
confidence: 99%
“…Over a century after its introduction, our basic knowledge of this uncommon tumor is still developing. In 2009 Kurokawa et al 10 showed that pilomatricomas could differentiate not only toward the hair follicle matrix cells but also toward the hair cortex, infundibulum, outer root sheath, and hair bulge.…”
mentioning
confidence: 99%